2007
DOI: 10.1159/000100110
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Serum Values of Soluble Intercellular Adhesion Molecule-1 and Total Sialic Acid Levels in Patients with Breast Cancer

Abstract: Background: In this study, we aimed to investigate serum total sialic acid (TSA) and soluble intracellular adhesion molecule-1 (sICAM-1) levels in breast cancer patients to find a correlation with the cancer stage. Methods: The parameters from sera of 61 patients with breast cancer were measured. The concentrations of serum sICAM-1 and TSA were measured in serum samples from 61 patients with breast cancer and 25 healthy control subjects using enzyme-linked immunoassay and thiobarbituric acid method. Results: M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…Many recent studies reported higher values of serum glycoproteins in various types of malignant conditions that include malignant melanoma [24,25], breast cancer [18,26], colorectal [27], gynecological [16], oral cancers [28]. Therefore, present study results are in consonance with previously reported findings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Many recent studies reported higher values of serum glycoproteins in various types of malignant conditions that include malignant melanoma [24,25], breast cancer [18,26], colorectal [27], gynecological [16], oral cancers [28]. Therefore, present study results are in consonance with previously reported findings.…”
Section: Discussionsupporting
confidence: 93%
“…The level of different types of serum glycoproteins are maintained within a narrow range in health [10], but is elevated in many pathological conditions viz. tuberculosis [11], autoimmune disease [12], cardiovascular disease [13,14], diabetes mellitus [15], cancer of cervix [16], uterus [17] and breasts [18], and arthritis [19]. Thus, it is of great interest to identify and validate serum glycoproteins whose change in levels may provide new insight into cancer progression and may have utility as potential markers for cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…During inflammatory and immune responses, ICAM-1 expressed on endothelial cells (EC) associates with lymphocyte function-associated antigen-1 (LFA-1) and macrophage antigen-1 (Mac-1) presented on leukocytes easing the invasion of damaged tissue by immune cells [13]. Due to its presence on many cancer cell types [12,[14][15][16][17], up-regulation of its soluble form in cancer patients [18,19] and potential role in metastasis [16,20,21], ICAM-1 expression may serve as an important diagnostic tool for assessing tumor prognosis and progression as well as its potential as a target for therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Several prevalent case-control studies have observed higher circulating concentrations of sICAM-1 in cancer cases compared with controls for various cancer sites (1,7,8). Genetic studies have shown that some single nucleotide polymorphisms of the ICAM-1 gene were associated with an increased cancer risk (20)(21)(22)(23), although this point is debated (24).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistic studies have shown that ICAM-1 could stimulate angiogenesis and neovascularization (4,5) and promote tumor growth (3) and cell migration (6). In epidemiologic crosssectional studies, concentrations of sICAM-1 were elevated in patients with various cancers (1,7,8). However, prospective studies investigating the association between prediagnostic concentrations of sICAM-1 and cancer risk are lacking.…”
Section: Introductionmentioning
confidence: 99%